EFEKTIVITAS PENGGUNAAN SIMURELAY SEBAGAI MEDIA SIMULASI DALAM PEMBELAJARAN INSTALASI MOTOR LISTRIK - Kartini, Ridha; Maksum, Hasan; Novaliendry, Dony (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
ABSTRACT Vocational education, particularly in the field of Electrical Installation Engineering, requires a high level of practical skills, including electric motor installation. However, limitations in practical facilities, safety risks, and limited student exploration time often pose significant challenges in conventional learning at Vocational High Schools (SMKs). This study aims to examine the effectiveness of Simurelay, an Android-based simulation media, as an alternative for practical electric motor installation learning. The method used is a systematic review of 10 relevant studies published between 2014 and 2025. Data were analyzed using content analysis to identify improvements in conceptual understanding, procedural skills, and students’ practical readiness. The review results indicate that Simurelay consistently enhances the ability to read control diagrams, understand current flow, master component functions, and develop troubleshooting skills. This media also reduces cognitive load, strengthens mental models, increases students’ motivation and confidence, and provides a safe practice environment without equipment damage risk. The use of Simurelay supports learner-centered learning, integrating principles of multimedia learning, inquiry-based learning, and constructivism. Thus, Simurelay proves to be an effective, adaptive, and relevant pedagogical tool for modern vocational education and has the potential to expand the transformation of technical learning in SMKs. Further research is recommended to develop more advanced simulation features, integrate VR/AR, and evaluate the long-term impact on graduates’ workforce readiness. ABSTRAK Pendidikan vokasional, khususnya pada bidang Teknik Instalasi Tenaga Listrik, menuntut penguasaan keterampilan praktis yang tinggi, termasuk instalasi motor listrik. Namun, keterbatasan sarana praktik, risiko keselamatan, dan rendahnya waktu eksplorasi siswa sering menjadi hambatan signifikan dalam pembelajaran konvensional di Sekolah Menengah Kejuruan (SMK). Penelitian ini bertujuan menelaah efektivitas penggunaan Simurelay, sebuah media simulasi berbasis Android, sebagai alternatif pembelajaran praktik instalasi motor listrik. Metode yang digunakan adalah systematic review terhadap 10 penelitian relevan yang dipublikasikan antara 2014–2025. Analisis data dilakukan melalui content analysis untuk mengidentifikasi peningkatan pemahaman konseptual, keterampilan prosedural, dan kesiapan praktik siswa. Hasil review menunjukkan bahwa Simurelay secara konsisten meningkatkan kemampuan membaca diagram kontrol, memahami alur arus, menguasai fungsi komponen, serta keterampilan troubleshooting. Media ini juga menurunkan beban kognitif, memperkuat mental model, meningkatkan motivasi dan kepercayaan diri siswa, serta memungkinkan praktik aman tanpa risiko kerusakan alat. Penggunaan Simurelay mendukung pembelajaran learner-centered, mengintegrasikan prinsip multimedia learning, inquiry-based learning, dan constructivism. Dengan demikian, Simurelay terbukti menjadi media pedagogis yang efektif, adaptif, dan relevan untuk pendidikan vokasional modern, serta berpotensi memperluas transformasi pembelajaran teknik di SMK. Penelitian lebih lanjut disarankan untuk pengembangan fitur simulasi lebih kompleks, integrasi VR/AR, dan evaluasi dampak jangka panjang pada kesiapan kerja lulusan.